Cytokine storm in SARS-CoV-2 infection and the potential treatments - Ade Oktiviyari; Zinatul Hayati; Tjut Mariam Zanaria (Trends in Infection and Global Health, 2022)
Cytokine storm is one of main features during respiratory distress caused by COVID-19 infection. Acute Respiratory Distress Syndrome (ARDS) is directly linked with elevated number of COVID-19 mortality cases. Extreme amounts of pro-inflammatory cells are found in the lung of dead patients, mainly macrophages and IL-17 cells. A high level of IL-6 was found in the plasma COVID-19 patients and indicated the severity of diseases. Some other chemokines, such as CXCL10, IL6, CCL2, CXCL1, and CXCL5, were upregulated as well as in COVID-19 patients and regulate the disease. In this review, we discuss the feature of cytokine storms and the current treatments used. We found that IL-6 has a significant role in exacerbated patients’ condition, and the suppression of this cytokine most likely benefits the patient. Another treatment with various targets has been proposed and proven as effective as well. Some of them are corticosteroids, anakinra, plasmapheresis, and interferons.